Epidemiology and risk factors for typhoid fever in Central Division, Fiji, 2014–2017: A case-control study - Prasad, Namrata; Jenkins, Aaron P.; Naucukidi, Lanieta; Rosa, Varanisese; Sahu-Khan, Aalisha; Kama, Mike; Jenkins, Kylie M.; Jenney, Adam W. J.; Jack, Susan J.; Saha, Debasish; Horwitz, Pierre; Jupiter, Stacy D.; et al. (PLoS neglected tropical diseases, 2018)
Typhoid fever is endemic in Fiji, with high reported annual incidence. We sought to identify the sources and modes of transmission of typhoid fever in Fiji with the aim to inform disease control. We identified and surveyed patients with blood culture-confirmed typhoid fever from January 2014 through January 2017. For each typhoid fever case we matched two controls by age interval, gender, ethnicity, and residential area. Univariable and multivariable analysis were used to evaluate associations between exposures and risk for typhoid fever. We enrolled 175 patients with typhoid fever and 349 controls. Of the cases, the median (range) age was 29 (2-67) years, 86 (49%) were male, and 84 (48%) lived in a rural area. On multivariable analysis, interrupted water availability (odds ratio [OR] = 2.17; 95% confidence interval [CI] 1.18-4.00), drinking surface water in the last 2 weeks (OR = 3.61; 95% CI 1.44-9.06), eating unwashed produce (OR = 2.69; 95% CI 1.48-4.91), and having an unimproved or damaged sanitation facility (OR = 4.30; 95% CI 1.14-16.21) were significantly associated with typhoid fever. Frequent handwashing after defecating (OR = 0.57; 95% CI 0.35-0.93) and using soap for handwashing (OR = 0.61; 95% CI 0.37-0.95) were independently associated with a lower odds of typhoid fever. Poor sanitation facilities appear to be a major source of Salmonella Typhi in Fiji, with transmission by drinking contaminated surface water and consuming unwashed produce. Improved sanitation facilities and protection of surface water sources and produce from contamination by human feces are likely to contribute to typhoid control in Fiji.